Lack of formal regulatory definitions of off-label medication use in children: an analysis using agency inquiry and text mining - Gade, Christina; Lausten-Thomsen, Ulrik (Frontiers in Pharmacology, 2026)
ObjectivesThis study investigates the formal definitions of “off-label” medication use among five major Western regulatory authorities—FDA, EMA, Health Canada, MHRA, and TGA. The primary research question is whether these agencies provide explicit, official definitions of off-label use.DesignThe study employs a mixed-methods design, combining direct inquiries via standardized questionnaires with AI-assisted text mining of publicly available regulatory documents.SettingRegulatory agencies at a national level across North America, Europe, and Oceania.ParticipantsFive agencies, with data collected through direct contact and automated document analysis; no human participants were involved.InterventionAnalysing agency webpages and documents for sentences that resemble formal definitions, followed by manual review and categorization based on linguistic and contextual criteria.Main outcomeThe presence or absence of official definitions, the content and clarity of any definitional statements, and their prominence within regulatory documents.ResultNone of the agencies provide a formal, official definition of off-label use. However, all agencies’ publicly available documents contain statements that resemble definitions, generally describing off-label use as prescribing beyond the conditions approved by the drug’s marketing authorization. Despite similarities in language, the clarity and prominence of these statements vary across agencies.ConclusionThe lack of formal off-label definitions may contribute to legal ambiguity, clinical uncertainty, and challenges in guideline development, particularly affecting paediatric populations where off-label prescribing is common. The regulatory agencies should adopt clear, standardized official definitions of off-label use to improve transparency, legal coherence, and patient safety.